Hugo Wolf and his Mörike songs - Youens, Susan (Cambridge University Press, 2000)
Viennese composer Hugo Wolf produced one of the most important song collections of the nineteenth century when he set to music fifty-three poems by the great German poet Eduard Mörike. Susan Youens reappraises this singular collaboration to shed new light on the sophisticated interplay between poetry and music in the songs. Wolf is customarily described as 'the Poet's Composer', someone who revered poetry and served it faithfully in his music. Yet, as Youens reveals, this cliché overlooks the rich terrain in which his songs are often at cross purposes with his chosen poetry. Although Wolf did much to draw the world's attention to the neglected Swabian poet, his musical interpretation of the poetry was also influenced by his own life, psychology and experiences. This book examines selected Mörike songs in detail, demonstrating that the poems and music each have their own distinctive stories which at times intersect but also diverge.